Prognosis and Prognostic Factors of Patients with Emergent Cerclage: A Japanese Single-Center Study. (26th December 2021) - Kobayashi, Ami; Takahashi, Hironori; Matsubara, Shigeki; Baba, Yosuke; Nagayama, Shiho; Ogoyama, Manabu; Horie, Kenji; Suzuki, Hirotada; Usui, Rie; Ohkuchi, Akihide; Fujiwara, Hiroyuki
Abstract : Objectives . The aims of this study were to clarify the following: (1) how often does prolonged pregnancy ≥34 weeks occur in patients with emergent cerclage without progesterone and (2) the risk factors preventing such pregnancy continuation. Materials and Methods . This retrospective observational study was performed using medical records of patients for whom emergent cerclage had been performed between April 2006 and December 2018 in our institute. Results . Emergent cerclage was performed in 123 patients (median age: 34, interquartile range: 31–36). Primiparous patients numbered 44 (36%). A history of spontaneous preterm birth (SPTB) was present in 30 (24%). The median presurgical cervical length (CL) was 16 (8–21) mm at surgery. Of the 123, 20 (16%) were delivered at 33 + 6 weeks or less (<34 weeks). We conducted logistic regression analysis of the risk factors of SPTBs <34 weeks after cerclage. Three risk factors were identified that increased the risk of SPTB <34 weeks: presurgical CL 0 mm (odds ratio (OR): 5.30; 95% confidence interval (CI): 1.58–17.7), a history of SPTB (OR: 4.65; 95% CI: 1.38–15.7), and the presence of sludge (OR: 4.14; 95% CI: 1.20–14.3). Conclusion . Three risk factors predicted SPTB <34 weeks after emergency cerclage without progesterone administration: unmeasurable CL (CL 0 mm), a history of SPTB, and the presence of sludge on ultrasound. SPTB <34 weeks occurred after emergency cerclage in 16% of patients, being comparable with the recent data with progesterone.